2021
DOI: 10.1101/2021.01.25.21249974
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergence and fast spread of B.1.1.7 lineage in Lebanon

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) remains a rapid spread emerging disease. Recently, a new variant of this virus called SARS-CoV-2 VOC 202012/01 (or B.1.1.7 lineage), described in the United Kingdom (UK), has become highly prevalent in several countries. Its rate of transmission has been estimated to be greatly higher. B.1.1.7 lineage harbors 23 mutations co-existed for the first time in the same variant. Herein, we are interested only by the deletion mutation ΔH69/ΔV70 in the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…In the UK, B.1.1.7 is now the predominant lineage, accounting for >90 % of infections [95]. In many countries, initially imported B.1.1.7 is rapidly outcompeting local strains and becoming the major circulating strain [96–99]. B.1.1.7 contains seven non-synonymous mutations in the spike glycoprotein and a total of 23 mutations across the whole genome (see ).…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, B.1.1.7 is now the predominant lineage, accounting for >90 % of infections [95]. In many countries, initially imported B.1.1.7 is rapidly outcompeting local strains and becoming the major circulating strain [96–99]. B.1.1.7 contains seven non-synonymous mutations in the spike glycoprotein and a total of 23 mutations across the whole genome (see ).…”
Section: Introductionmentioning
confidence: 99%
“…Genome sequencing is the gold method to confirm the new variant, but observational studies provide also stronger evidence if similar models are observed in multiple countries, especially when randomized studies are not possible. In Lebanon, surveillance data from Beirut Medical Center and Bahman Hospital showed a rapid and dramatic increase in S-negative profile in PCR testing for SARS-CoV-2 in the first twelve days in January, reaching approximately 60% of positive cases and 95% in February [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in different countries, including the US, Germany, Spain, Denmark, and the United Kingdom, found that the B.1.1.7 lineage is more likely than the original virus to send infected patients to the hospital and is also more deadly [111][112][113] [115]. Furthermore, over a 12-day period in January, the number of patients with B.1.1.7 grew rapidly at a hospital and cardiac center in Lebanon, and the proportion of COVID-19 cases with "spike gene target failure" or "spike gene drop out" (SGTF increased from 16 to 60% [116]; SGTF refers to positive test with a non-detectable S gene Ct value and Ct ≤ 30 for N and ORF1ab targets [117]. A Swedish research group revealed that Alpha-positive persons had considerably greater rates of hospitalization (2.6% vs. 1.2%) and severe illness than negative individuals, although the numbers were too small to assess differences in severity rates among hospitalized individuals [118].…”
Section: Disease Severitymentioning
confidence: 99%